2014
DOI: 10.2466/29.30.pms.118k22w1
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Blood Lactate Levels in Equestrians Performing Show Jumping

Abstract: In equestrian show jumping, attention is particularly important to ensure maximum accuracy. Due to the anaerobic nature of the jumping and its requirement for precision coordination between human and horse, there may be a relation between the onset of lactic threshold and decrease in attention. In 12 healthy and injury-free equestrians (6 men, 6 women), the effects (blood lactate and glucose) of a show jumping course (250 m long with eight vertical obstacles with a height of 1.15 m height) on capacity and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…It is widely accepted that people who practice high-risk sports in the long-term frequently regulate emotion and anxiety, and in this way reinforce their capability for emotion control (14,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). It may be useful to investigate the ways in which individuals learn strategies of self-regulation from a high-risk context, and whether and how they transfer these skills to everyday life situations.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that people who practice high-risk sports in the long-term frequently regulate emotion and anxiety, and in this way reinforce their capability for emotion control (14,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). It may be useful to investigate the ways in which individuals learn strategies of self-regulation from a high-risk context, and whether and how they transfer these skills to everyday life situations.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 Also in equestrian performing show jumping, a deterioration of attention (intensity and selectivity) and a worsening of performance were observed only when blood lactate exceeds OBLA. 36 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, if on the one hand an increase of blood lactate is associated with an improvement in the excitability of the primary motor cortex [12,19,20], on the other hand it is concomitant to a worsening of attentional capabilities involving the prefrontal cortex [1,21,22]. Furthermore, experiment carried out with visual- [9] and somatosensory-evoked potentials [23] has shown that increases of blood lactate are associated, in both cases, with an improvement in the conduction time between the periphery and the primary sensory areas and a worsening of intracortical communication between primary areas and adjacent regions.…”
Section: Discussionmentioning
confidence: 99%